1996
DOI: 10.1016/s0378-1097(96)00414-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Rhodococcus rhodochrous NCIMB13064 derivatives with new biodegradative abilities

Abstract: NCIMBl3064 can dehalogenate and utilise a number of halogenated aliphatic compounds as sole carbon and energy source. Mutants of NCIMB13064 can be easily isolated with an enlarged range of I-chloroalkane utilising ability. Dehalogenation of 1-chlorononane, I-chlorodecane and short-chain I-chloroalkanes (C&B) is encoded by the same plasmid pRTL1. However, a different genetic element(s) is required for the dehalogenation of 3-chloropropionic acid. Two derivatives (PZOO and P400) of R. rhodochrour NCIMB13064 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…I24, the TKN14 NidA and NidB proteins had high amino acid homology to the large and small subunits of naphthalene dioxygenases (NDOs) found in various Rhodococcus species;, i.e., two subspecies (P200 and P400) derived from Rhodococcus rhodochrous NCIMB13064 (DDBJ/EMBL/GenBank accession nos. AY392424 and AY392423) (19,21), Rhodococcus sp. NCIMB12038 (accession no.…”
Section: Resultsmentioning
confidence: 99%
“…I24, the TKN14 NidA and NidB proteins had high amino acid homology to the large and small subunits of naphthalene dioxygenases (NDOs) found in various Rhodococcus species;, i.e., two subspecies (P200 and P400) derived from Rhodococcus rhodochrous NCIMB13064 (DDBJ/EMBL/GenBank accession nos. AY392424 and AY392423) (19,21), Rhodococcus sp. NCIMB12038 (accession no.…”
Section: Resultsmentioning
confidence: 99%
“…Rhodococcus strains NCIMB12038, P200, and P400 have been described previously (16,20). Escherichia coli strain DH5␣ and plasmid vector pBluescript KS(ϩ) were used for the cloning experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Both subunits of the NCIMB12038 NDO showed approximately 30% amino acid identity to the corresponding P. putida NDO subunits, with conservation of the key catalytic residues (19). Rhodococcus strains P200 and P400 were shown to degrade naphthalene via catechol and catechol-2,3-dioxygenase activity and not via the gentisate route (16).…”
mentioning
confidence: 99%
“…Although Rhodococcus species utilize naphthalene as their sole carbon and energy source, [82][83][84][85] to the best of our knowledge, the PAH catabolic genes from these have not been characterized until recently. Larkin et al 86) reported the puriˆcation and characteristics of a novel ISP of naphthalene dioxygenase from Rhodococcus sp.…”
Section: )mentioning
confidence: 99%